Dinamika Pasar Komoditas Pangan Strategis: Analisis Fluktuasi Harga Dan Produksi - Ida Marina; Dety Sukmawati; Edang Juliana; Zahra Nur Safa (Paspalum: Jurnal Ilmiah Pertanian, 2024)
This study was conducted in Garut Regency to evaluate the production and prices of strategic food commodities. The goal is to provide data to stakeholders to manage food needs. The research method used time series data analysis of agricultural production and prices collected from relevant agencies. The analysis results showed significant production fluctuations in several key commodities such as large red chili, cayenne pepper, and shallots. These fluctuations affect the prices of food commodities, especially cayenne pepper which experiences high fluctuations. The research also highlights the importance of price management to maintain regional economic stability. Changes in food commodity prices have an important impact, helping the government forecast inflation and serving as a selling price guideline for traders. However, delays in information on price fluctuations can make it difficult for the public and related parties to make decisions. Therefore, efforts are needed to provide better and more timely market information. With complete information, the government and market players can take appropriate steps to maintain economic stability and adequate food availability for the community. This shows the importance of analyzing data on food commodity price changes in decision-making and policy planning at the national level.